Perkembangan Metode Pembelajaran Sejarah Kebudayaan Islam di Era Modern melalui Tinjauan Analisis Bibliometrik Tahun 2020-2024 - Hidayah, Siti Nor; Junaidi, Junaidi; Arliansyah, Arliansyah (YASIN, 2025)
In the context of modern education, learning the history of Islamic culture is faced with challenges to be delivered effectively, therefore teachers need methods that are relevant to the needs of students. The purpose of this research is to find out the development of Islamic cultural history methods in the modern era from 2020-2024 using bibliometric methods. Data collection was carried out with the help of the publish or perish application to access papers from Google Scholar, with the keyword “Islamic cultural history method” traced in the title. This data was then inputted into VOSviewer software to perform co-occurrence analysis. The analysis through VOSviewer was carried out with two types of visualization, namely network visualization and overlay visualization. The results of this study show a significant increase in the number of publications from 2021 to reach its peak in 2023 on the method of Islamic cultural history. The results of the Network Visualization bibliometric analysis show the diversity of methods applied in learning the history of Islamic culture. This diversity of methods illustrates the adaptation of teaching to the needs of learning in the modern era is very varied as an effort to accommodate different learning needs and adapt to the times. Meanwhile, the results of the Overlay Visualization analysis show that research trends in Islamic cultural history learning methods continue to develop from year to year with more interactive and innovative methods such as role playing methods, team quiz, and resitation methods.